2017
DOI: 10.1063/1.4979123
|View full text |Cite
|
Sign up to set email alerts
|

A general theoretical description of the influence of isotropic chemical shift in dipolar recoupling experiments for solid-state NMR

Abstract: We present a general theoretical description that allows to describe the influence of isotropic chemical shift in homonuclear and heteronuclear dipolar recoupling experiments in magic-anglespinning solid-state NMR. Through a transformation of the Hamiltonian into an interaction frame with the combined radio-frequency irradiation and the isotropic chemical shift, we determine an effective Hamiltonian to first order with respect to the relevant internal nuclear spin interactions. This unravels the essential reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…However, this is not computationally practical, and we have chosen a value for time T , such that it is longer than both 2π/ω eff and 2π/ω m , to ensure the convergence on the value of aχfalse(italick,italiclfalse). Alternatively, the coefficients can be determined efficiently using a more advanced method introduced recently ( 31 ). The analytical description of the interaction-frame transformation and the calculation of the Fourier coefficients (Eq.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is not computationally practical, and we have chosen a value for time T , such that it is longer than both 2π/ω eff and 2π/ω m , to ensure the convergence on the value of aχfalse(italick,italiclfalse). Alternatively, the coefficients can be determined efficiently using a more advanced method introduced recently ( 31 ). The analytical description of the interaction-frame transformation and the calculation of the Fourier coefficients (Eq.…”
Section: Introductionmentioning
confidence: 99%
“…For dipolar couplings under magic-angle spinning, we have demonstrated that a similar representation leads to accurate simulation results. 30 However, the aim here is to simplify matters even more, so we hypothesize that the AB-spin system Hamiltonian using the effective J coupling is a good approximation for the present system. We will not use this approximation for precise numerical calculations, but we will use it to establish more qualitative measures of the performance of different pulse sequences.…”
Section: Articlementioning
confidence: 99%
“…A similar result was found for the much larger dipole-dipole interaction under magic-angle spinning. 30 However, convergence and the possible necessity for including higher-order terms is a concern in some cases and will be the subject of a future-ongoing-study.…”
Section: Single-spin Operators In the Flipped Framementioning
confidence: 99%
See 1 more Smart Citation
“…Following this, a phase-alternating low-power X-inverse X (XiX)-DNP has been demonstrated recently using similar average Hamiltonian and operator-based Floquet theory design principles 30 . In this work, we further introduce an alternative design strategy based on single-spin vector effective Hamiltonian theory 31,32 , which incorporates Fourier coefficients (exploited in Floquet theory) into average Hamiltonian theory. This theoretical framework is applicable to any arbitrary periodic DNP experiments, and will here be used for designing broadband DNP experiments.…”
Section: Introductionmentioning
confidence: 99%